PENERAPAN IFRS DAN HUBUNGANNYA DENGAN KOMPARABILITAS PENGUNGKAPAN ASET TETAP PADA LAPORAN KEUANGAN PERUSAHAAN - Setianto, Ardian; Juliarto, Agung (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
The objective of this research is to analyze the implementation of IFRS and its relationship with thedisclosure comparability of fixed assets or now called PPE (Property, Plant, and Equipment) inthe financial statements. The variables used in this study is the application of IFRS which focusedon disclosure comparability of PPE. This research is based on previous research conducted byVergauwe and Gaeremynck (2013). The sample of this research was manufacturing companywhich listed on the Indonesian Stock Exchange (IDX) in the year 2011-2013. Data were collectedby using purposive sampling method and 327 observation data were analyzed. The hypothesistesting in this research utilized multiple regression analysis with SPSS Release 20. The resultsof this analysis finds that the coefficient of the interaction variable between initial property,plant, and equipment (PPE) disclosure index and the application period of IFRS in first year andsecond year is become increasingly negative. It indicates that the differences of PPE disclosurelevel among firms are decreased. This suggests that the differences of PPE disclosures level in thefinancial statements among firms become smaller over time resulting in higher comparability asthe enactment of IFRS convergence.